2022
DOI: 10.3390/jcm11206011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Differences and Outcomes of COVID-19 Associated Pulmonary Thromboembolism in Comparison with Non-COVID-19 Pulmonary Thromboembolism

Abstract: (1) Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has been reported to increase the risk of pulmonary thromboembolism (PTE). The aim of this study is to elucidate whether Coronavirus disease COVID-19-associated PTE has a different clinical expression than non-COVID-19 PTE due to a different pathophysiology. (2) Methods: retrospective study of PTE episodes conducted at our hospital between January 2019 and December 2020, comparing the group of COVID-19-associated PTE patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
1
0
0
1
Order By: Relevance
“…Similarly, a New York Health System reported patients with COVID-19 WPE had a mortality rate of 20%, which is parallel to our study [14]. Cossio et al reported that in comparison to non-COVID PE, Patients with COVID-19 with PE were less likely to have classic risk factors and symptoms of venous thromboembolism, however no mortality difference was noted at 1 year [15]. Similarly, Miro et al replicated the same results as Cossio et al, however in-hospital mortality was 16% in COVID-19-related PE vs. non-COVID PE.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, a New York Health System reported patients with COVID-19 WPE had a mortality rate of 20%, which is parallel to our study [14]. Cossio et al reported that in comparison to non-COVID PE, Patients with COVID-19 with PE were less likely to have classic risk factors and symptoms of venous thromboembolism, however no mortality difference was noted at 1 year [15]. Similarly, Miro et al replicated the same results as Cossio et al, however in-hospital mortality was 16% in COVID-19-related PE vs. non-COVID PE.…”
Section: Discussionsupporting
confidence: 87%
“…Si bien la infección pulmonar y la inmovilidad son factores de riesgo clásicos para la aparición de enfermedad tromboembólica, 4 se ha descrito un aumento de la incidencia de 2 a 4 veces en pacientes con diagnóstico de COVID-19. 5,6 Ello ha planteado la existencia de factores de riesgo específicos asociados a la infección viral. Diversos mecanismos fisiopatológicos se han descrito en tromboembolismo pulmonar en pacientes COVID-19, como la aparición de multímeros de alto peso molecular de factor von Willebrand y la NETosis de neutrófilos como marcadores de disfunción endotelial; 7-9 además de los factores sistémicos propios de la infección por SARS-COV-2 como son el estado proinflamatorio e inmovilidad asociada a la hospitalización.…”
Section: Introductionunclassified